2021
DOI: 10.3390/ani11041115
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Drainage Mapping with Indirect Lymphography for Canine Mammary Tumors

Abstract: Mammary gland tumors are the most common canine neoplasms. They account for 25–50% of all tumors diagnosed in bitches. Metastases and recurrences develop in about 35–70% of bitches following excision. The presence of regional lymph node metastases is a relevant factor affecting prognosis and treatment in cases of mammary gland tumors. The sentinel lymph node (SLN) is the first lymph node (or nodes) in the regional lymphatic basin that receives lymphatic flow from the primary neoplasm. The aim of this study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…Additionally, the combined use of ultrasonographic characteristics in malignancy prediction was not explored. Considering the lymphatic system’s importance for metastasis, future research should also include the draining lymph nodes and investigate the potential role of CEUS in the detection of metastases [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the combined use of ultrasonographic characteristics in malignancy prediction was not explored. Considering the lymphatic system’s importance for metastasis, future research should also include the draining lymph nodes and investigate the potential role of CEUS in the detection of metastases [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Absence of efficient prognosis protocols is related to complexity of interpretation of the data due to application of different methods of studying tumour components (Matos et al, 2012). Taking into account that metastases and relapses develop in around 35-70% of bitches after surgical treatment (Collivignarelli et al, 2021), evaluating the prognostic markers is the key element to improve the therapeutic strategies for treating cancer patients (Boracchi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In a multi-center retrospective study, Burrai et al (2020) demonstrated that the most significant factors of the prognosis are the size of the tumour and age of the animal. Presence of metastases in the regional lymph nodes is an important factor influencing the prediction and treatment in cases of mammary tumours (Collivignarelli et al, 2021). Yamagami et al (1996) observed no significant differences in the survival of bitches with different subtypes of adenocarcinomas (tubular, papillary and cystic papillary).…”
Section: Introductionmentioning
confidence: 98%
“…The sentinel lymph node (SLN), defined as the first lymph node on the drainage pathway of a tumor, may differ from the anatomically closest regional lymph node (RLN) in 22–63% of tumor-bearing dogs [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ], and metastases to the SLN have been reported in up to 50–70% of dogs, depending on the tumor type [ 2 , 4 , 5 , 6 , 9 , 10 , 11 , 12 ]. Given the well-accepted impact of the accurate detection of nodal metastases on staging and treatment recommendations, the implementation of sentinel lymph node biopsy (SLNB) in the surgical management of canine malignancies has gained increased interest in recent years [ 8 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%